The philosophy of John scottus eriugena : - Moran, Dermot (Cambridge University Press, 2004)
Moran has written the most comprehensive study yet of Eriugena's philosophy, tracing the sources of his thinking and analyzing his most important text, the Periphyseon. This volume will be of special interest to historians of mediaeval philosophy, history, and theology.